Eighth Grade Students' Geometric Writing Ability Based on Van Hiele's Theory in the Geogebra-Assisted PBL Model - Rizkya Ramadhani, Anya; Junaedi , Iwan (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Geometric writing ability is part of written mathematical communication abilities that focus on representing mathematical ideas in written form. Research observations show that this ability is still relatively low among eighth-grade students. The Geogebra-assisted Problem-Based Learning model is considered effective in encouraging active student engagement. Van Hiele's theory was chosen to classify students' geometric thinking stages. The purpose of this study was to describe the geometric writing ability of eighth-grade students based on Van Hiele's theory through the application of the Geogebra-assisted Problem-Based Learning model. The method used in this study was descriptive qualitative. The population in this study were eighth-grade students of SMP Negeri 32 Purworejo in the 2024/2025 academic year, with a purposive sampling technique. The instruments used included the Van Hiele geometry level test questions and interview guidelines. Data analysis was done by reducing the data, presenting the data, and drawing conclusions/verification. The results of this study are (1) the Van Hiele geometry level test results show that most students are at stage 2 (informal deduction), and (2) there are differences in students' geometric writing abilities based on groups, with the upper group able to achieve three of the four indicators, the middle group able to achieve two of the four indicators, and the lower group only able to achieve one of the four indicators. Based on these results, it is found that Van Hiele's theory, the PBL model, and Geogebra can help develop students' geometric writing ability.